Integrated evaluation of road transport pollution impact on the urban air - Šerevičienė, Vaida; Vasiliauskienė, Vaida; Paliulis, Dainius; Aleknaitė, Jurgita (International Conference “Environmental Engineering”, 2017)
With the number of vehicles increasing, the analysis of urban air pollution becomes expedient. This article deals with the integrated evaluation of road transport realised pollutant impact on the urban air. During research, it was carried out complex measurements of the air quality involving passive diffusive sampling for nitrogen dioxide, active measurement for particle matters, lichen sampling for heavy metals and visual assessment of trees defoliation. Obtained results showed the statistically reliable (p < 0.05) strong correlation (r = 0.83) between the number of passing vehicles and the concentration of particulate matter and there is even stronger correlation (r = 0.94; p < 0.05) between the con centration of nitrogen dioxide and the number of passing vehicles. It was observed during the analysis, that in measuring sites in which was determined 30% more intense defoliation process, also determined a higher NO2 (>10 / m3) and lead (~10 mg/kg) concentrations. It can be argued that the source of mentioned pollutants is the same – motor transport, and their presence in the environment influences defoliation phenomenon.
Keywords: air pollution; nitrogen dioxide; particle matter; heavy metals; defoliation